The prevalence of nomophobia in Cyprus and its relationship with coping styles - Mousoulidou, Marilena; Constantinidou, Erietta; Christodoulou, Andri; Siakalli, Michailina (Frontiers in Psychology, 2025)
IntroductionThe rise in smartphone use and the resulting dependence has led to the emergence of nomophobia, a term describing the anxiety or discomfort experienced when individuals are without their mobile phones. This study aimed to examine the prevalence of nomophobia among adults in Cyprus and explore its relationship with demographic characteristics, reasons for smartphone use, and coping styles.MethodsIn line with this aim, participants were 300 adults from Cyprus recruited by convenience and snowball sampling methods. The data were collected via an internet-based questionnaire that examined participants' level of nomophobia, reasons for phone use, time spent on their phones, and coping styles. The study utilized a Personal Information Form, the Nomophobia Questionnaire (NMP-Q), and the Brief Coping to Problems Experienced Inventory (Brief COPE) to gather data.ResultsThe results suggest that (a) nearly all participants (99.3%) exhibited some level of nomophobia, with more than half of our sample (51.3%) experiencing moderate levels, (b) younger adults, women, and individuals with lower education levels were more prone to nomophobia, (c) communication and social media were positively related to nomophobia, and (d) maladaptive and avoidant coping strategies exacerbated the severity of nomophobia.DiscussionThe findings highlight the growing concern of nomophobia and stress the need for educational programs promoting healthier smartphone habits.